Sistem Penyemprot Hexacopter Bertali (Tethered): Untuk Pertanian Presisi - Al, Al (ITP Press, 2026)
The implementation of Unmanned Aerial Vehicles (UAVs) in the agricultural sector has undergone a paradigm shift from passive monitoring to active functional intervention. However, limited battery autonomy and flight instability induced by dynamic payload variations remain critical bottlenecks for large-scale industrial adoption. This paper presents a systematic review of the evolution of agricultural UAVs, focusing on the emergence of tethered hexacopter systems (TKT-6) as a robust solution for persistent, long-duration missions in complex topographies. We synthesize high-impact research (2021–2025) covering high-voltage power transmission, umbilical cable dynamics, and advanced control architectures. A primary emphasis is placed on the transition from conventional PID frameworks to adaptive-robust control strategies. Comparative analysis reveals that the synergy between Disturbance Observers (DOB) and Sliding Mode Control (SMC) significantly mitigates attitude errors and suppresses the